the Analisis Faktor Pengaruh Minat Penggunaan Sistem Informasi Akuntansi Berbasis E-commerce Shopee Pada Mahasiswa Akuntansi Surakarta: Analisis Faktor Pengaruh Minat Penggunaan Sistem Informasi Akuntansi Berbasis E-commerce Shopee Pada Mahasiswa Akuntansi Surakarta - Faradila, Diana; Hudi Kurniawanto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
In this study, to analyze the interest factors in using e-commerce-based accounting information systems among Surakarta private students. This research is quantitative research. The population of this research is private students from Surakarta. The sample determination technique uses the Slovin formula. Data analysis uses SPSS 25. The results of this study prove that perceived ease and trust influence interest in the Shopee e-commerce based accounting information system and perceived risk does not influence interest in using the Shopee e-commerce based accounting information system. So, Shopee e-commerce features must pay attention to service, privacy & security and provide functional features so that they can attract students' attention to use Shopee e-commerce.